Multiparentalidade: análise da efetivação do princípio da dignidade humana no julgamento do Recurso Extraordinário nº 898060 pelo Supremo Tribunal Federal - Paiva, Christianne Matos de (2019)
The social and economic changes of the end of the twentieth century and the beginning of the twenty-first century distressed family entities and, consequently, paternity and maternity. The law, affected by so many meta-juridical amendments, has faced new questions concerning Family Law with the aid of the Constitutional Civil Law. In this cluster of recent family problematizations, multiparenting, a theme of the general repercussion 622, was chosen as the research object of this thesis, in which field of study refers to social inclusion, protection and defense of human rights. The purpose of this thesis is to address the following problem: How were the contents of the arguments made in the Federal Supreme Court (STF) ruling in the Extraordinary Appeal nº 898060 for the recognition in the legal framework of multiparenting built? For this, the study of human dignity, family, paternity was contextualized, next the STF ruling was analyzed from the perspective of the considered hypothesis, that is: the arguments issued in the ruling on multiparenting were built based on the effectiveness of the principle of human dignity upon the specificities of concrete cases. The thesis is structured in five chapters, introduction and conclusion. In this regard, a qualitative descriptive approach was made and as a methodological procedure, a content analysis was used under Laurence Bardin's guidelines, in order to understand the explicit or non-apparent meanings in the content of the discussions. In the typology, bibliographic and documentary research were used, this as the study of materials from various sources, in this case the votes of the justices, since the examination of jurisprudence was an indispensable vector for the construction of the thesis. Regarding the procedural methods, the historical method was utilized, to verify the evolution of some institutes, the comparative through the analysis of similar cases with the paradigmatic decision of the STF and the deductive. The results of the study point towards the edification of the arguments for the thesis to be intended to human dignity effectiveness with the limits imposed by the particularities of concrete cases based on the Constitutional Civil Law.